Posterior Reversible Encephalopathy Syndrome Associated with FOLFOX Chemotherapy - Luiz Carlos Porcello Marrone; Bianca Fontana Marrone; Tharick Ali Pascoal; Lucas Porcello Schilling; Ricardo Bernardi Soder; Sheila Schuch Ferreira; Giovani Gadonski; Jaderson Costa da Costa (Case Reports in Oncological Medicine)
Posterior reversible encephalopathy syndrome (PRES) is a clinicoradiologic entity characterized by headaches, altered mental status, seizures, visual loss, and characteristic imaging pattern in brain MRI. The cause of PRES is not yet understood. We report a case of a 27-year-old woman that developed PRES after the use of FOLFOX 5 (oxaliplatin/5-Fluoracil/Leucovorin) chemotherapy for a colorectal cancer.